Kebijakan Pendidikan Islam di Indonesia: Masa Kolonial Hingga Masa Reformasi - Eva Tri Cahyanti (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2021)
Abstract: This article will examine the study of Islamic education policies in the archipelago from the colonial period to the present. The purpose of writing this article is to find out how the policies are implemented in Indonesia from time to time. This research is a descriptive study with library research methods. The conclusion from this research is that during the colonial period, Islamic education in Indonesia experienced discrimination and was always neglected. This can be seen from the goals of the colonizers who were none other than their interests. Islamic educational institutions also always accept distinctions, including the implementation of madrasas and Islamic boarding schools. The dualism of education in Indonesia was more clearly seen when visiting the Dutch colonials, developing missionary schools, and implementing Christianization efforts as a whole in the archipelago. After achieving independence, Islamic education in Indonesia began to experience many changes and progress. The existence of equalization of levels and status of schools, school curriculum, and learning strategies have also become more varied, modern, and even adopted from the western education system. Abstrak: Artikel ini akan mengkaji dinamika kebijakan Pendidikan Islam di Nusantara mulai masa penjajahan kolonial hingga saat ini. Tujuan penulisan artikel ini adalah untuk mengetahui bagaimana kebijakan-kebijakan yang diterapkan di Indonesia dari masa ke masa. Penelitian ini merupakan penelitian lualitatif deskriptif dengan metode library research. Kesimpulan yang didapat dari penelitian ini yaitu pada masa penjajahan, pendidikan Islam di Indonesia mengalami diskriminasi dan selalu dianaktirikan. Hal tersebut terlihat dari tujuan bangsa penjajah yang tidak lain untuk kepentingan mereka sendiri. Lembaga pendidikan Islam juga selalu menerima pembedaan, termasuk upaya penyelenggaraan madrasah dan pesantren. Dualisme pendidikan di Indonesia semakin jelas terlihat saat dengan terangterangan penjajah Belanda mengembangkan sekolah misionaris dan menerapkan upaya kristenisasi secara menyeluruh di wilayah nusantara. Setelah mencapai kemerdekaan, pendidikan Islam di Indonesia mulai mengalami banyak perubahan dan kemajuan. Adanya penyetaraan jenjang dan status sekolah, kurikulum pelajaran sekolah dan strategi pembelajaran juga menjadi lebih variatif, modern bahkan banyak mengadopsi dari sistem penyelenggaraan pendidikan barat.